Organophotoredox-catalyzed decarboxylative C-O/N/S bond formation: access to ampakine APIs and quinazolinone alkaloids - Sonavane, Sameer R.; Kale, Tushar B.; Bhatt, Gaurang J.; Mhaske, Santosh B. (Organic Letters, 2025)
This study describes a novel and general protocol featuring organophotoredox-catalyzed intramolecular decarboxylative construction of carbon-heteroatom (oxygen, nitrogen, and sulfur) bonds, enabling direct access to ampakine APIs (CX-614 and CX-554), quinazolinone alkaloids (deoxyvasicinone and mackinazolinone), and thiazinone scaffolds as well as their congeners with broad functional group tolerance and scalability. Mechanistic studies suggest a radical-polar crossover pathway via single-electron oxidation.